2014
DOI: 10.1002/ijc.28748
|View full text |Cite
|
Sign up to set email alerts
|

A new insight into fecal hemoglobin concentration‐dependent predictor for colorectal neoplasia

Abstract: We sought to assess how much of the variation in incidence of colorectal neoplasia is explained by baseline fecal hemoglobin concentration (FHbC) and also to assess the additional predictive value of conventional risk factors. We enrolled subjects aged 40 years and over who attended screening for colorectal cancer with the fecal immunochemical test (FIT) in Keelung community-based integrated screening program. The accelerated failure time model was used to train the clinical weights of covariates in the predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
31
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 26 publications
3
31
1
Order By: Relevance
“…This work has been subsequently extended and f-Hb has been demonstrated to be an independent predictor of the risk of colorectal neoplasia (12). In Scotland, it has been documented that f-Hb is related to detection of AN in the next screening round and it was clearly stated that studies of f-Hb and outcomes over screening rounds might provide strategies to direct available colonoscopy towards those at highest risk (13).…”
Section: Editorialmentioning
confidence: 96%
“…This work has been subsequently extended and f-Hb has been demonstrated to be an independent predictor of the risk of colorectal neoplasia (12). In Scotland, it has been documented that f-Hb is related to detection of AN in the next screening round and it was clearly stated that studies of f-Hb and outcomes over screening rounds might provide strategies to direct available colonoscopy towards those at highest risk (13).…”
Section: Editorialmentioning
confidence: 96%
“…While fecal immunochemical test (FIT) has become an early detection method for colorectal cancer in population‐based screening program (Benson et al, ) with the axiom that the concentration of fecal hemoglobin (f‐Hb), one kind of antibody to human hemoglobin, can be detected from feces in an quantitative manner. There are three previous studies demonstrating the dose‐response effects of f‐Hb on the risk of incident neoplasia (Chen, Yen, Chiu, Liao, & Chen, ; Yen et al, ) and to colorectal cancer (CRC) mortality (Chen et al, ). The recent two studies also found the positive associations between f‐Hb concentration and periodontal probing depth (Amy, Lai, Fann, Chiu, & Chen, ), and also inflammatory bowel disease (Kato, Hiraoka, & Nakarai, ), which is a chronic inflammation disorders of the intestine (Rubin, Shaker, & Levin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that incorporate risk assessment into the screening algorithm show the potential for improved test accuracy of the FIT . For example, Stegeman et al .…”
mentioning
confidence: 99%
“…Studies that incorporate risk assessment into the screening algorithm show the potential for improved test accuracy of the FIT [8,[16][17][18]. For example, Stegeman et al investigated combining risk factors with the FIT result when selecting individuals for colonoscopy referral in a Dutch population [16].…”
mentioning
confidence: 99%